Early Childhood Economic Education Model to Suppress Consumerism (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The International Community Service held in the Kuala Lumpur Indonesian School aims to increase students' understanding of Financial Literacy. Departing from the phenomenon of the lack of outreach to early childhood and elementary school students regarding the importance of saving and the high level of consumerism in today's society, educators (lecturers) and students from the University of North Sumatra through presentations, discussions, and simulation on how to use a savings book tries to introduce how the concept of Financial Literacy in a simple way, how to distinguish wants or needs and how to manage finances to students who are in the Indonesian School of Kuala Lumpur. This project aims to support students' knowledge about it. The urgency to introduce the concept of financial literacy education to children, especially preschool and elementary students, will make children accustomed to managing finances properly and correctly in the future. Implementing this program is expected to increase students' knowledge of financial literacy, increase their enthusiasm to be more sensitive to economic conditions, and encourage them to get used to a culture of saving to avoid excessive consumerism in the future.